Postsurgical Prosthetic Rehabilitation after Mandibular Ameloblastoma Resection: A 7-Year Follow-Up Case Report - C. Moreno-Soriano; A. Estrugo-Devesa; P. Castañeda-Vega; E. Jané-Salas; J. López-López (Case Reports in Dentistry)
Ameloblastomas are benign but locally invasive odontogenic tumors most frequently located in the mandible. The gold standard of treatment is the surgical resection of the tumor with safety margins. Postsurgical defects generate a significant morbidity that needs reconstruction and oral rehabilitation to restore the oral functions. This case report describes the prosthetic rehabilitation of a 42-year-old male after resection of a mandibular ameloblastoma. Excision of the lesion by segmental mandibulectomy and mandibular reconstruction by microvascularized fibula flap was performed. After placement of 6 dental implants, the patient was rehabilitated with a lower hybrid prosthesis fabricated using computer-aided design-computer-aided manufacturing. During a 7-year and 5-month follow-up, some clinical complications were observed.